Co-administration of Oral Cholera Vaccine With Oral Polio Vaccine Among Bangladeshi Young Children: A Randomized Controlled Open Label Trial to Assess Interference. (22nd September 2022) - Islam, Md Taufiqul; Date, Kashmira; Khan, Ashraful Islam; Bhuiyan, Taufiqur Rahman; Khan, Zahid Hasan; Ahmed, Shamim; Hossain, Motaher; Khaton, Fatema; Zaman, K; McMillan, Nigel A J; Anand, Abhijeet; An, Qian; et al.
Abstract: Background: Cholera remains a public health threat for low- and middle-income countries, particularly in Asia and Africa. Shanchol™, an inactivated oral cholera vaccine (OCV) is currently in use globally. OCV and oral poliovirus vaccines (OPV) could be administered concomitantly, but the immunogenicity and safety of coadministration among children aged 1–3 years is unknown. Methods: We undertook an open-label, randomized, controlled, inequality trial in Dhaka city, Bangladesh. Healthy children aged 1–3 years were randomly assigned to 1 of 3 groups: bivalent OPV (bOPV)-alone, OCV-alone, or combined bOPV + OCV and received vaccines on the day of enrollment and 28 days later. Blood samples were collected on the day of enrollment, day 28, and day 56. Serum poliovirus neutralizing antibodies and vibriocidal antibodies against Vibrio cholerae O1 were assessed using microneutralization assays. Results: A total of 579 children aged 1‒3 years were recruited, 193 children per group. More than 90% of the children completed visits at day 56. Few adverse events following immunization were recorded and were equivalent among study arms. On day 28, 60% (90% confidence interval: 53%–67%) and 54% (46%–61%) of participants with co-administration of bOPV + OCV responded to polioviruses type 1 and 3, respectively, compared to 55% (47%–62%) and 46% (38%–53%) in the bOPV-only group. Additionally, >50% of participants showed a ≥4-fold increase in vibriocidal antibody titer responses on day 28, comparable to the responses observed in OCV-only arm. Conclusions: Co-administration of bOPV and OCV is safe and effective in children aged 1–3 years and can be cost-beneficial. Clinical Trial Registration: ClinicalTrials.gov (NCT03581734). Abstract : Co-administration of bivalent oral poliovirus vaccine (bOPV) and oral cholera vaccine (OCV) is safe and effective in children aged 1–3 years and can be cost-beneficial. The study results are useful when bOPV and OCV are likely to be co-administered such as integrated OPV and OCV campaign. Clinical Trial Registration : ClinicalTrials.gov (NCT03581734)